Shared decision‐making in routine breast cancer care in Germany—A cross‐sectional study. Issue 7 (10th February 2022) - Feiten, Stefan; Scholl, Isabelle; Dünnebacke, Jan; Schmidt, Marcus; Franzen, Arno; Ernst, Walter; Spaderna, Heike; Weide, Rudolf
Abstract: Objective: Many preference‐sensitive decisions have to be made in breast cancer care and little is known about the decision‐making processes between breast cancer patients and the different health care professionals engaged in their treatment. Methods: All female breast cancer patients who underwent surgery in four German breast centers between 07/2016 and 12/2018 were invited to fill in a survey. The decision‐making process was evaluated using the 9‐item Shared Decision Making Questionnaire (SDM‐Q‐9) and a German measure to assess satisfaction with care (ZAPA). The higher the total score (0–100), the higher the experienced degree of participation and satisfaction, respectively. Participants were asked to separately rate consultations with their inpatient hospital doctors, outpatient gynecologists, outpatient oncologists and primary care providers. An overall mean score for the degree of participation and the satisfaction with care was calculated for each patient across all consultations assessed. Differences between the 4 treating physician groups were analyzed as well. Results: Of 1068 approached patients, 563 with a mean age of 62 and a standard deviation (SD) of 12.2 years filled in the survey (response rate: 53%). The overall SDM‐Q‐9 score was 73.8 (SD: 20.8). Older patients stated a higher level of participation than younger, different physician groups were rated quite similarly. Overall satisfaction with care was 87.4 (SD: 15.5). Conclusions: Overall, patients reported to have experienced a high level of shared decision‐making (SDM) and were quite satisfied with their treatment. However, we do not know whether non‐responders might have had different experiences.